Bats and grammar: developing critical language awareness in the context of school reform. Issue 4 (12th November 2018) - Gebhard, Meg; Graham, Holly
Abstract : Purpose: This paper aims to analyze how middle schoolers developed a critical awareness of language while participating in a curricular unit informed by systemic functional linguistics (SFL). This unit was developed to understanding and taking action to protect a local bat population in the context of school reforms shaping teaching and learning in the USA. It was designed to support a heterogeneous class of seventh graders in learning to read scientific explanations, write letters to government officials and develop a functional metalanguage to support them in analyzing how language simultaneously constructs ideas, enacts power dynamics and manages the flow of information in disciplinary texts. The questions guiding this study are: How do students use SFL metalanguage in text production and interpretation practices? Do their uses of SFL metalanguage support critical language awareness and reflection? And, if so, in what ways? Design/methodology/approach: This study uses ethnographic methods to conduct teacher action research. Data include classroom transcripts, student writing samples and interviews. Findings: The findings illustrate how students engaged with SFL, often playfully, to create their own student-generated functional metalanguage in highly productive ways. Research limitations/implications: This study contributes to a growing body of scholarship that suggests SFL metalanguage can provide teachers and students with a powerful semiotic toolkit that enables them to navigate the demands of teaching and learning in the context of the Standardization and Accountability movement. Practical implications: This study has implications teachers' professional development and students' disciplinary literacy development in the context of school reform. Originality/value: To date, few studies have explored how students take up and transform SFL metalanguage into a tool for critical reflection, especially adolescents.